1988
DOI: 10.1161/01.hyp.11.4.371
|View full text |Cite
|
Sign up to set email alerts
|

An impedance method for blood pressure measurement in awake rats without preheating.

Abstract: SUMMARY The tail-cuff methods for measuring systolic blood pressure in the rat usually require preheating of the animal to obtain recordable pulse signals. To find a more sensitive method, we applied the principle of differentiated impedance (dZ/dt) to the tail-cuff measurement of systolic blood pressure. We obtained clear pulse signals from the tail in awake rats without preheating the animals, and the systolic blood pressure obtained by this method had an excellent correlation with the directly measured femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…[1][2][3][4] Several groups have attempted to develop improved tail-cuff methods, such as integrating the use of a lamp lens to localize the heating stimulus to the tail rather than to the whole animal, 7) or by employing electrical impedance to avoid animal heating altogether. 8) However, these methods still require specialized apparatus, which limits their widespread use. The goal of this study was to assess the validity of a novel tail-cuff method that does not require animal heating (method A).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several groups have attempted to develop improved tail-cuff methods, such as integrating the use of a lamp lens to localize the heating stimulus to the tail rather than to the whole animal, 7) or by employing electrical impedance to avoid animal heating altogether. 8) However, these methods still require specialized apparatus, which limits their widespread use. The goal of this study was to assess the validity of a novel tail-cuff method that does not require animal heating (method A).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of arterial blood pressure Determination of mean arterial blood pressure was performed by impedance analysis of the electrical tail resistance using tail-cuff compression [39], recently modified for mice in this institute. A lock-in amplifier was used to obtain a high resolution at the given signal-to-noise ratio [18].…”
Section: Determination Of Urinary Corticosterone Concentrationmentioning
confidence: 99%
“…AP is fixed at the moment of disappearance of the pulse wave as far as air is injected in the cuff. It was demonstrated that the results of AP measurements by the sphygmographical (indirect) method and by direct cannulation of arteries provide similar results in the studies conducted on rats (Wen et al, 1988). AP can be measured by the indirect method (by means of the cuff worn on the animal tail) both in adult rats (Bunag and Batterfield, 1982;Wen et al, 1988) and in young rats at the age 1.5 months (Amstislavsky et al, 1998) and even at the age 3 weeks (Markel et al, 1999).…”
Section: Methods Of Arterial Pressure Measurementmentioning
confidence: 57%